Tackling multimorbidity: patient characteristics and outcomes from a generic rehabilitation programme. (2nd April 2022) - Cowie, Aynsley; McKay, Janet; Holt, Jane; Baylis, Moray
Abstract : Background/Aims: This service evaluation analyses the first 3 years of a novel 10-week generic rehabilitation programme, describing the cohort population assessed at baseline, and examining outcomes generated by programme completion. The programme is part of a wider specialist-generalist health and social care model, based within Ayrshire, Scotland, which has been designed to be a sustainable approach to tackling multimorbidity. Methods: Sociodemographic and diagnostic data were obtained for all service users who attended for baseline assessment. Two groups were compared: those who completed the 10-week programme (completers group) and those who did not (assessment+ group). Quality of life data were obtained from the completers group at the start and end of the 10-week programme, while emergency bed days accrued in the 12 months pre- and post-referral were recorded from both groups. Results: Over 3 years, n =978 service users attended for assessment (mean age 66.3 years; male:female ratio 441:537 [45%:55%]; average of four co-existing conditions). Deprivation was significantly higher for the assessment+ group ( P =0.003). The completers group demonstrated significant improvements across various quality of life outcomes ( P <0.001), and significantly reduced emergency bed days ( P =0.005; P =0.001) following the programme. Conclusions: In this generic multimorbidity rehabilitation programme, the baseline population was older adults, comprised slightly more women than men, and who had presented with complex multimorbidity. Deprivation was significantly higher in those who did not complete the programme, and further qualitative and quantitative exploration of this group is required. Completing the programme appeared to significantly improve quality of life and unscheduled care use.